Science, abduction and the fuzzy nurse: an exploration of expertise. - Rolfe G (Journal of Advanced Nursing (Wiley-Blackwell))
Benner's work on expertise in nursing drew heavily on the writing of Dreyfus and Dreyfus in the field of computing. Dreyfus and Dreyfus argued that the continued failure of computer programmers to create an 'expert system', a program which could replicate the way that a human expert thinks, implied that experts do not think in a rational, analytic way. Dreyfus and Dreyfus therefore concluded that expertise is an intuitive process, and that 'the expert is simply not following any rules! He is... recognising thousands of special cases'. Applied to nursing, this model of expertise has a number of profound implications for practice and education, and has been criticised for being elitist and deliberately obscure. This paper examines some recent innovations in computer logic, and argues that nursing can learn from a new breed of 'fuzzy' computer programmes which appear to be able not only to perform better than experts, but to verbalize their decision-making processes. By beginning to understand how experts think, it might be possible to develop expertise in a more controlled and logical way, thereby improving the practice of nursing.